Large-amplitude, circularly polarized, compressive, obliquely propagating electromagnetic proton cyclotron waves throughout the earth’s magnetosheath: Low plasma β conditions - Remya, B.; Tsurutani, B. T.; Reddy, R. V.; Lakhina, G. S.; Falkowski, B. J.; Echer, E.; Glassmeier, K. -H. (My University, 2014)
During 1999 August 18, both Cassini and WIND were in the Earth's magnetosheath and detected transverse electromagnetic waves instead of the more typical mirror-mode emissions. The Cassini wave amplitudes were as large as ~14 nT (peak to peak) in a ~55 nT ambient magnetic field B 0. A new method of analysis is applied to study these waves. The general wave characteristics found were as follows. They were left-hand polarized and had frequencies in the spacecraft frame (f scf) below the proton cyclotron frequency (fp ). Waves that were either right-hand polarized or had f scf > fp are shown to be consistent with Doppler-shifted left-hand waves with frequencies in the plasma frame fpf < fp . Thus, almost all waves studied are consistent with their being electromagnetic proton cyclotron waves. Most of the waves (~55%) were found to be propagating along B 0 ($\theta _{kB_{0}}<30^{\circ}$), as expected from theory. However, a significant fraction of the waves were found to be propagating oblique to B 0. These waves were also circularly polarized. This feature and the compressive ([B max – B min]/B max, where B max and B min are the maximum and minimum field magnitudes) nature (ranging from 0.27 to 1.0) of the waves are noted but not well understood at this time. The proton cyclotron waves were shown to be quasi-coherent, theoretically allowing for rapid pitch-angle transport of resonant protons. Because Cassini traversed the entire subsolar magnetosheath and WIND was in the dusk-side flank of the magnetosheath, it is surmised that the entire region was filled with these waves. In agreement with past theory, it was the exceptionally low plasma β (0.35) that led to the dominance of the proton cyclotron wave generation during this interval. A high-speed solar wind stream (langVsw rang = 598 km s–1) was the source of this low-β plasma.
Keywords: Instabilities and methods